Evaluation of cortisol levels in gingival crevicular fluid and saliva in anxious and non-anxious patients with chronic periodontitis - Sangeeta Umesh Nayak; Dilip G Nayak; Ashita S Uppoor; K Keshava Pai (Wolters Kluwer Medknow Publications, 2013)
Background: To evaluate gingival crevicular fluid (GCF) and salivary cortisol levels in anxious and non-anxious patients with chronic periodontitis. Materials and Methods: A total of 45 patients with a mean age 43.4 ± 6.12 years were assigned to three groups: Healthy control group (Group 1), group with chronic periodontitis but no anxiety (Group 2) and group with chronic periodontitis and with anxiety (Group 3). State - Trait anxiety inventory and Hamilton Anxiety rating scale were used to assess the anxiety levels of all the subjects. Clinical measures such as plaque index (PI), gingival index (GI), probing pocket depth (PPD) and clinical attachment level (CAL) were recorded. GCF and unstimulated whole saliva samples were collected, and cortisol levels were determined using ELISA kit. Results: PI, GI, PPD, and CAL were higher in Group 3. Hormone level was significantly higher in Group 3. A positive correlation was found among salivary and GCF cortisol and CAL in Group 3. Conclusion: Based on the obtained results individuals with high-levels of anxiety seem to be more prone to have periodontal disease. Salivary and GCF cortisol levels can be used as biomarker for evaluating part of the etiopathogenesis of chronic periodontitis.